Students as Users of Digital Libraries - Catlow, John; Górny, Mirosław; Lewandowski, Rafał (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
We present the results of a survey of one category of users of Polish digital libraries, namely students. This group accounts for 20% of all users. We begin by describing the way in which Polish students make use of digital libraries: how often they visit such a library, how long a typical session lasts, what materials are used most frequently, and what percentage of the total literature they use comes from digital libraries. This is followed by results concerning students’ evaluations and expectations of digital libraries. They were asked, among other things, to assess the mechanisms available for search and retrieval, and the quality of the scans. The degree of trust accorded to digital publications was also investigated.